Requerimiento de los pasivos financieros bajo el marco NIIF Grupo Dos, Pymes del sector alojamiento y servicios de comida del municipio de Palmira, Valle del Cauca (2021)
This monographic preliminary draft has as general objective and fundamental research purpose, to identify the different technical requirements that SME entrepreneurs in the accommodation and food service sector of the municipality of Palmira must consider for the management of their financial liabilities under the Accounting Framework Niif.